Media and development - Vokes, Richard (London ; New York : Routledge/Taylor & Francis, 2018)
"The text provides advanced undergraduate, and postgraduate, students with an introduction to the key theoretical perspectives in both media theory and development studies. It also brings these two bodies of theory into dialogue with each other, by examining the ways in which both media and development produce social changes (both intended and unintended), and by looking at how media has been, and could be, 'harnessed' by development agencies, developing world governments, NGOs, and peoples in the developing world as part of their wider attempts to achieve positive social change"--
Bibliography: p.261-281
Includes bibliographical references and index.
Keywords: Mass media -- Developing countries